PENERAPAN MODEL KOOPERATIF TIPE INQUIRI PADA PEMBELAJARAN IKATAN KIMIA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR - YUNI NOER SYAMSIYAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The activity level of students in class X IPA 2 SMAN 10 Pandeglang before the study was 12.5% ??and the average learning outcome was 42.4. Inquiry type cooperative learning provides many opportunities for students to express opinions, ask and answer questions, so that all students can be actively involved in the learning process. The application of the inquiry type cooperative learning model is able to provide learning experiences about various phenomena or facts so that students are able to conclude or find answers that are certain in accordance with the objectives of using inquiry learning strategies, namely developing the ability to think systematically, logically and critically. This study aims to improve student activity and learning outcomes in chemical bonding learning through the inquiry type cooperative learning model. This classroom action research consists of 2 cycles, with 4 stages, namely planning, implementation, observation and reflection. It was carried out on 32 students of class X IPA 2 of SMAN 10 Pandeglang in the 2017/2018 academic year. Based on the results of the study, it turned out that student activity increased by 43.62% from the first cycle of 38.18% and 81.8% in the second cycle. This shows that the application of the inquiry-type cooperative learning model can increase student activity. Student learning outcomes in the cognitive domain also increased by 43.75%, which came from the first cycle of 34, 38% and the second cycle of 78.13%. In general, the results showed that the application of the inquiry-type cooperative learning model could improve student activity and learning outcomes in chemical bonding learning at SMAN 10 Pandeglang. ABSTRAKTingkat keaktifan siswa kelas X IPA 2 SMAN 10 Pandeglang sebelum penelitian sebesar 12,5% dan rata-rata hasil belajarnya 42,4. Pembelajaran kooperatif tipe inquirí banyak memberikan kesempatan siswa saling mengemukakan pendapat, bertanya dan menjawab, maka semua siswa dapat terlibat aktif dalam proses pembelajaran. Penerapan model pembelajaran kooperatif tipe inquirí mampu memberikan pengalaman belajar tentang berbagai fenomena atau fakta sehingga siswa mampu menyimpulkan atau menemukan sendiri jawaban yang sudah pasti sesuai dengan tujuan dari penggunaan strategi pembelajaran inquirí yaitu mengembangkan kemampuan berpikir secara sistematis, logis dan kritis. Penelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar siswa pada pembelajaran ikatan kimia melalui model pembelajaran kooperatif tipe inquirí. Penelitian tindakan kelas ini terdiri atas 2 siklus, dengan 4 tahap yaitu perencanaan, pelaksanaan, pengamatan dan refleksi. Dilakukam pada 32 siswa kelas X IPA 2 SMAN 10 pandeglang tahun pelajaran 2017/2018. Berdasarkan hasil penelitian, ternyata aktivitas siswa meningkat 43,62% yang berasal dari siklus I sebesar 38,18% dan 81,8% pada siklus II. Hali ini menunjukkan bahwa penerapan model pembelajaran kooperatif tipe inquirí dapat meningkatkan aktivitas siswa. Hasil belajar siswa pada ranah kognitif juga meningkat sebesar 43,75% yang berasal dari siklus I sebesar 34, 38% dan siklus II sebesar 78,13%. Secara umum hasil penelitian menunjukkan bahwa penerapan model pembelajaran kooperatif tipe inquirí dapat meningkatkan aktivitas dan hasil belajar siswa dalam pembelajaran ikatan kimia di SMAN 10 Pandeglang.